Voltage and Frequency Control in Renewable Rich Microgrid - Valiyev, Mehdi (ADA University, 2023)
The increasing integration of renewable energy sources into microgrids has resulted in a fundamental transformation of the power distribution framework. This study examines the essential elements of voltage and frequency boundaries in microgrids with a significant amount of renewable energy sources, focusing on the specific difficulties arising from the intermittent and variable characteristics of renewable energy generation. In the context of the global shift towards sustainable energy solutions, it is of the highest priority to comprehend and proficiently handle the voltage and frequency dynamics within microgrids. Renewable powered microgrids, which involve the incorporation of sources such as photovoltaics, wind turbines, and energy storage devices, exhibit a dynamic and complicated operational setting. In contrast to traditional power systems, the fluctuating nature of renewable energy generation requires the use of sophisticated control mechanisms in order to ensure the voltage and frequency remain within acceptable thresholds. This thesis highlights the importance of employing advanced control algorithms capable of accommodating the natural oscillations associated with renewable power generation. The exploration of voltage regulation is conducted within the framework of reactive power control and voltage support provided by inverters. Similarly, the examination of frequency regulation involves the coordination of energy storage systems and intelligent inverters. The analysis of the interplay among these variables is conducted in order to obtain full insights into the operational dynamics of microgrids that have a high proportion of renewable energy sources. In addition, this discourse addresses the difficulties associated with upholding grid resilience and stability in light of the intermittent characteristics of renewable energy sources. It emphasizes the significance of adopting a comprehensive methodology that integrates sophisticated control tactics, energy storage systems, and communication technologies.In summary, this study makes a valuable contribution to the current scholarly conversation surrounding the effective administration of voltage and frequency in microgrids that include a significant presence of renewable energy sources. The results emphasize the importance of using novel control systems and incorporating advanced technologies to effectively tackle the distinct issues associated with the shift towards sustainable energy sources. The findings reported in this paper provide significant recommendations for engineers, researchers, and politicians who are interested in improving the dependability and performance of microgrid systems in the context of the growing adoption of renewable energy worldwide.
Keywords: Microgrids -- Voltage regulation -- Frequency regulation.; Renewable energy sources -- Integration; Energy storage systems -- Control; Photovoltaic systems -- Power generation; Wind power -- Integration; Global energy transition; IT and Engineering; IT and Engineering